The effectiveness of using learning CDs on increasing information and communication technology learning outcomes - Ketut Susiani; I Nengah Suastika; Dewa Bagus Sanjaya (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
The era of revolution 4.0 requires educators and students to have skills that are able to compete globally. One of the skills that are becoming a trend today is digital literacy. Mastery of communication technology is one of the subjects that are able to answer these challenges. The purpose of this study was to determine the effectiveness of using Learning CDs in information and communication technology subjects. By using quantitative and design methods pseudo used in the study this is a Randomized Two - group Design Posttest Only analyzed with statistical formulas, it was found that the results of learning technology information and communication groups of students who are taught using learning CDs experience a significant increase.